Exploring International Student Academic Discourse Socialization in Canadian Universities through a Deleuzian Lens - Gene Vasilopoulos (Canadian Society for Studies in Education, 2016)
As Canadian universities set their sights on increasing their international student populations, a critical re-examination of research approaches to international student language and adjustment to Western higher education is imperative. This paper draws on Deleuzian ontology of difference to better understand the complex and rapidly changing milieu of higher education. More specifically, it critically re-examines the application of the well-established academic discourse socialization framework in view of a changing academic community. It challenges the notion of a uniform, linear process of socialization based on essentialized identities of novice / expert. By introducing Deleuzian concepts of "becoming," "assemblage," and "language," prevailing constructs of identity, academic community, and academic discourse are transformed into interconnected ever-changing entities, working together in potentially unpredictable ways.